In-situ online detection method for parameters in curing process of crack filling slurry for stone cultural relics

Through the use of optical fiber Bragg grating sensors, an online detection system for the curing process of stone cultural relics grouting materials has been built, which solves the problem of difficulty in real-time detection of temperature, humidity and microstrain in the existing technology, and realizes all-round monitoring of the restoration process of stone cultural relics.

CN119533533AActive Publication Date: 2025-02-28CHONGQING UNIV OF TECH

Patent Information

Application Number
CN202411446457.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-28
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

It is difficult for existing testing technologies to conduct in-situ real-time online in-situ detection of key parameters such as temperature, humidity and micro-strain of the grouting materials of stone cultural relics.

Method used

Optical fiber Bragg grating is used to prepare fiber temperature-sensitive sensors, fiber strain sensors and fiber humidity-sensitive sensors, and through the combination of integrated packaging and modem, an online detection system is built to collect and monitor the temperature, humidity and strain of the filling slurry in real time.

Benefits of technology

Real-time online detection of the curing process parameters of the crack filling slurry of stone cultural relics is achieved, comprehensive monitoring data is provided, and the efficiency and accuracy of the restoration and protection of stone cultural relics is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119533533A_ABST
    Figure CN119533533A_ABST
Patent Text Reader

Abstract

The invention discloses a stone cultural relic crack filling slurry curing process parameter in-situ online detection method, which comprises the following steps: respectively preparing an optical fiber temperature-sensitive sensor, an optical fiber strain sensor and an optical fiber humidity-sensitive sensor by adopting an optical fiber Bragg grating, and integrally packaging each sensor to obtain a filling slurry curing process parameter detection device; a plurality of prepared filling slurry curing process parameter detection devices are adopted and are vertically placed at different height positions in the cracks of the stone cultural relics respectively, each filling slurry curing process parameter detection device is connected to a corresponding signal input end of a modulation-demodulation instrument, and when filling slurry is injected into the cracks of the stone cultural relics, the modulation-demodulation instrument is connected with the corresponding signal input end of the modulation-demodulation instrument. Drift data of center wavelengths corresponding to all sensors in all filling slurry curing process parameter detection devices are collected through a modulation-demodulation instrument and demodulated; and then demodulated data information is transmitted to a computer, and the computer calculates parameters of the filling slurry curing process at different height positions of the stone cultural relic crack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stone cultural relic restoration, and in particular to an in-situ online detection method for parameters of a curing process of a slurry for filling cracks in stone cultural relics. Background Art

[0003] Among the common methods used to repair stone cultural relics, grouting repair is the most traditional and effective repair method. It can fill the huge cracks caused by geological movement according to the size of the cracks, and can also finely repair surface cracks. It can effectively repair and reinforce the internal structure of stone cultural relics to ensure their safety and reliability.

[0004] The detection technology of grouting materials for stone cultural relics is mainly divided into two types: online detection and offline detection.

[0005] Among them, offline detection mainly includes X-ray diffraction, Fourier infrared spectroscopy and scanning electron microscopy. Among them, X-ray diffraction can perform non-destructive analysis on the crystal structure of the internal materials of stone cultural relics, evaluate the matching degree between the repair materials and the original materials, and thus monitor the repair effect and material stability. Fourier infrared spectroscopy can obtain important information about the chemical composition and structural characteristics of the grouting materials of stone cultural relics, which is helpful to evaluate its applicability, stability and impact on the preservation of cultural relics. Scanning electron microscopy technology testing of stone cultural relics grouting materials can provide important information about the microstructure and performance of the materials. However, offline detection technology requires advance processing of samples and is costly and time-consuming.

[0006] Online detection mainly includes nuclear magnetic resonance testing, infrared thermal imaging and optical microscopy. The application of nuclear magnetic resonance testing in grouting tests can track the hydration process of grouting materials in real time and observe the diffusion of slurry in rock pores and cracks. Infrared thermal imaging technology can provide a fast and non-destructive means for the detection of grouting materials for stone cultural relics, helping to evaluate the performance and effect of grouting materials, and thus guiding restoration and protection work. Optical microscopy can obtain the visible spectrum image of the slurry after magnification.

[0007] In general, the existing detection technology is difficult to achieve online in-situ real-time detection of key parameters such as temperature, humidity and micro-strain during the curing process of grouting materials. Therefore, studying a detection method suitable for key parameters of the curing process of grouting materials for stone cultural relics can provide important support for evaluating the effectiveness of rock crack disease treatment of stone cultural relics and provide major help for improving the efficiency of stone cultural relics crack treatment. Summary of the invention

[0008] The present invention aims to provide an in-situ online detection method for parameters of the curing process of a slurry filling crack in stone cultural relics, so as to solve the technical problem that in the process of repairing stone cultural relics by grouting repair, the existing detection technology is difficult to achieve online in-situ real-time detection of key parameters such as temperature, humidity and micro-strain in the curing process of the grouting material.

[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0010] The invention discloses an in-situ online detection method for parameters of a curing process of a slurry for filling cracks in stone cultural relics, comprising the following steps:

[0011] S1. Using fiber Bragg gratings to prepare fiber temperature sensors, fiber strain sensors, and fiber humidity sensors, respectively, and calibrating the fiber temperature sensors, fiber strain sensors, and fiber humidity sensors, respectively, to establish the relationship between temperature and the central resonance wavelength of the fiber Bragg grating in the fiber temperature sensor, the relationship between strain and the central resonance wavelength of the fiber Bragg grating in the fiber strain sensor, and the relationship between humidity and the central resonance wavelength of the fiber Bragg grating in the fiber humidity sensor;

[0012] S2, integrating the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor prepared in step S1 to obtain a device for detecting parameters of the filling slurry curing process;

[0013] S3, building an online detection system for the curing process parameters of the filling slurry in the cracks of stone cultural relics, using multiple filling slurry curing process parameter detection devices prepared in step S2, and vertically placing them at different heights in the cracks of stone cultural relics, respectively, so that the placement positions remain unchanged; connecting each filling slurry curing process parameter detection device to the corresponding signal input terminal of the modem, and connecting the signal output terminal of the modem to the signal input terminal of the computer;

[0014] S4, preparing a filling slurry, and uniformly injecting the filling slurry into the cracks of the stone cultural relics under constant temperature and humidity conditions;

[0015] S5. The drift data of the central wavelengths corresponding to the optical fiber temperature sensor, the optical fiber strain sensor and the optical fiber humidity sensor in each filling slurry curing process parameter detection device are collected by a modem, and demodulated to obtain demodulated data information; the demodulated data information is then transmitted to a computer, and the computer calculates the filling slurry curing process parameters at different height positions of the stone cultural relic crack according to the relationship between temperature and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber temperature sensor, the relationship between strain and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber strain sensor, and the relationship between humidity and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber humidity sensor, wherein the filling slurry curing process parameters include the temperature change, strain change and humidity change of the filling slurry during the curing process.

[0016] Specifically, the filling slurry curing process parameters include the temperature, humidity and microstrain of the filling slurry.

[0017] This scheme discloses a fiber optic detection method for the temperature, humidity and micro-strain of the slurry (such as water glass slurry) filling the cracks of stone cultural relics during the solidification process. The method uses a fiber Bragg grating temperature sensor, a fiber Bragg grating strain sensor and a fiber Bragg grating humidity sensor to perform online in-situ measurement of the temperature, humidity and micro-strain of the filling slurry curing process in the simulated sandstone cultural relic cracks.

[0018] During detection, the optical fiber humidity sensor mainly responds to three changes in the temperature, humidity and micro-strain inside the slurry. The strain sensor mainly responds to two changes in the temperature and strain inside the slurry. The optical fiber temperature sensor only responds to the temperature change information of the slurry. The optical fiber temperature sensor has two functions. The first function is to measure the temperature change during the slurry curing process. The second function is to serve as a temperature compensation unit for the strain sensor and the optical fiber humidity sensor to eliminate the influence of the slurry temperature change on the strain and humidity measurement results. The strain sensor has two functions. The first function is to measure the strain change inside the slurry curing. The second function is to serve as a strain compensation unit for the optical fiber humidity sensor to eliminate the influence of the slurry strain change on the humidity measurement results.

[0019] The present invention will provide important support for evaluating the effectiveness of treating rock fissure diseases in stone cultural relics, and has great scientific significance and engineering application value.

[0020] Preferably, in step S1, the optical fiber temperature sensor is used to monitor the temperature of the slurry curing process and eliminate the influence of temperature on the humidity and strain detection results, that is, the optical fiber temperature sensor is used as a temperature compensation unit of the optical fiber humidity sensor and the optical fiber strain sensor while being used as an optical fiber temperature sensor; the optical fiber temperature sensor is prepared by the following method: an untreated bare fiber Bragg grating is used, and then a stainless steel capillary is used to seal and package the grating area of ​​the bare fiber Bragg grating to obtain a fiber temperature sensor; before packaging, the bare fiber Bragg grating is temperature calibrated to establish the relationship between the temperature and the central resonant wavelength of the bare fiber Bragg grating to achieve accurate temperature detection and temperature compensation.

[0021] The purpose of using a stainless steel capillary to encapsulate the grating region of the bare fiber Bragg grating is to eliminate the influence of stress on the detection result during the detection process; at the same time, the two ends are sealed with epoxy resin glue to prevent the filling slurry from entering the stainless steel capillary during the detection process.

[0022] Preferably, in step S2, the optical fiber strain sensor is used to monitor the strain of the filling slurry curing process and eliminate the influence of the strain on the humidity detection result, that is, the optical fiber strain sensor is used as a strain compensation unit of the optical fiber humidity sensor while being used as an optical fiber strain sensor; the optical fiber strain sensor adopts an untreated bare fiber Bragg grating.

[0023] Preferably, in step S3, the optical fiber humidity sensor is prepared by the following method:

[0024] A1. Use a bare fiber Bragg grating and pre-process the bare fiber Bragg grating, wherein the bare fiber Bragg grating comprises a core, the core has a grating region, the outer periphery of the core is coated with a cladding, the outer periphery of the cladding is coated with a coating layer, and the cladding and coating layer structure corresponding to the grating region are removed;

[0025] A2, treating the pretreated fiber Bragg grating with silane to enhance the adhesion strength of the fiber Bragg grating surface;

[0026] A3, preparing chitosan-polyvinyl alcohol moisture-sensitive material to obtain chitosan-polyvinyl alcohol hydrogel;

[0027] A4. Evenly apply chitosan-polyvinyl alcohol hydrogel on the peripheral surface corresponding to the grating area of ​​the fiber Bragg grating treated with silane, and then dry it to form a humidity-sensitive film on the peripheral surface corresponding to the grating area of ​​the fiber Bragg grating, thereby obtaining an optical fiber humidity-sensitive sensor.

[0028] Preferably, in step A3, the chitosan-polyvinyl alcohol humidity-sensitive material is prepared by the following method:

[0029] A3.1. Add chitosan powder to glacial acetic acid solution and stir evenly at room temperature to obtain chitosan solution;

[0030] A3.2. Add polyvinyl alcohol powder to deionized water and stir evenly in a water bath to obtain a polyvinyl alcohol solution;

[0031] A3.3. Add the polyvinyl alcohol solution dropwise into the prepared chitosan solution and stir evenly at room temperature to obtain chitosan-polyvinyl alcohol hydrogel.

[0032] Preferably, in step A3, the mass ratio of chitosan to polyvinyl alcohol is in the range of 4.5:1 to 7.2:1.

[0033] Preferably, in step A3.1, the mass fraction of the glacial acetic acid solution is in the range of 2% to 5%.

[0034] Preferably, in step A3.2, the mass fraction of the polyvinyl alcohol solution is in the range of 10% to 11%.

[0035] Preferably, in step S2, the integrated packaging of the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor is performed by the following method: a porous stainless steel tube is used to wrap the grating areas corresponding to the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor, and at the same time, the optical fiber pigtails corresponding to the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor extend from the same end of the porous stainless steel tube, and the tube wall of the porous stainless steel tube is evenly provided with a plurality of through holes; one end of each optical fiber pigtail extending out of the porous stainless steel tube is sealed.

[0036] The porous stainless steel tube can effectively protect each sensor during measurement. The purpose of sealing one end of the porous stainless steel tube is to fix each optical fiber pigtail so that the relative position between each optical fiber pigtail remains unchanged. In addition, during measurement, the filling slurry can enter the porous stainless steel tube from the other end and contact each sensor, so that the temperature, humidity and micro-strain at the same position can be measured simultaneously.

[0037] Preferably, in step S5, when the computer calculates the filling slurry curing process parameters at different height positions of the stone cultural relic cracks, the optical fiber temperature sensor and the optical fiber strain sensor are used as the temperature compensation unit and the strain compensation unit of the optical fiber humidity sensor respectively, and the pre-constructed matrix model is performed to obtain the filling slurry curing process parameters; the matrix model is:

[0038]

[0039] In the formula, ΔλB_1 is the total drift of the fiber Bragg grating wavelength of the fiber temperature sensor, Δλ B_2 is the total drift of the fiber Bragg grating wavelength of the optical fiber strain sensor, Δλ B_3 is the total drift of the fiber Bragg grating wavelength of the fiber humidity sensor, ΔT is the temperature change; Δε is the strain change, and ΔRH is the humidity change;

[0040] K T_1 is the fiber Bragg grating temperature sensitivity coefficient of the fiber temperature sensor, expressed as:

[0041]

[0042] K ε_1 , K T_2 are the fiber Bragg grating strain sensitivity coefficient and temperature sensitivity coefficient of the optical fiber strain sensor, respectively, expressed as:

[0043] K ε_1 =λ B-2 (1-P ε );

[0044]

[0045] K RH , K ε_2 and K T_3 The sensitivity coefficients of humidity, strain and temperature of the fiber Bragg grating of the optical fiber humidity sensor are respectively expressed as:

[0046]

[0047] K ε_2 =λ B_3 (1-P ε );

[0048]

[0049] In the above formula, λ B 1. Lambda B 2. Lambda B 3 represents the resonant center wavelength of the fiber Bragg grating in the fiber temperature sensor, fiber strain sensor, and fiber humidity sensor respectively; α is the thermal expansion coefficient of the fiber material, is the thermo-optical coefficient; P ε is the effective elastic-optical coefficient of the fiber Bragg grating, r f is the fiber radius; t is the thickness of the humidity sensitive film, C0 is the surface bonding coefficient between the fiber grating and the humidity sensitive film, E M and E f are the Young's modulus of the moisture-sensitive material film and the optical fiber, αM(RH) is the moisture expansion coefficient of the humidity sensitive film, A M and A f are the cross-sectional areas of the moisture-sensitive material film and the optical fiber respectively; α M(T) and α f(T) are the thermal expansion coefficients of the humidity sensitive film and optical fiber, respectively.

[0050] The present invention has the following beneficial effects:

[0051] The invention solves the technical problem that in the process of repairing stone cultural relics by grouting repair, the existing detection technology is difficult to realize online in-situ real-time detection of key parameters such as temperature, humidity and micro-strain in the curing process of grouting materials. The technical solution of the invention can simultaneously monitor multiple key parameters such as temperature, humidity and strain of the filling slurry, and provides comprehensive monitoring data for the repair and protection of stone cultural relics. The fiber Bragg grating sensor is very sensitive to changes in temperature, humidity and strain, can detect tiny changes, and has high sensitivity. The fiber optic sensor is not affected by electromagnetic interference, can work stably in complex electromagnetic environments, has strong anti-interference ability, and has good long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to make the purpose, technical solution and advantages of the invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings, in which:

[0053] Figure 1 It is a schematic diagram of the structure of the optical fiber temperature sensitive sensor of the present invention.

[0054] Figure 2 It is a schematic diagram of the structure of the optical fiber humidity sensor of the present invention.

[0055] Figure 3 It is a schematic structural diagram of a device for detecting parameters of a filling slurry curing process according to the present invention.

[0056] Figure 4 It is a schematic diagram of the composition of the on-line detection system for parameters of the curing process of the slurry for filling cracks in stone cultural relics of the present invention.

[0057] Figure 5 The temperature variation curves inside the water glass slurry at different heights measured in the embodiments of the present invention are shown in FIG.

[0058] Figure 6 The following are the humidity variation curves of the water glass slurry at different heights measured in the embodiments of the present invention.

[0059] Figure 7 The graphs are the internal stress variation curves of water glass slurry at different heights measured in the embodiments of the present invention.

[0060] Explanation of the reference numerals: 101, optical fiber temperature sensor; 102, optical fiber strain sensor; 103, optical fiber humidity sensor; 200, bare fiber Bragg grating; 201, fiber core; 202, grating region; 203, cladding; 204, coating layer; 205, stainless steel capillary; 206, humidity sensitive film; 300, device for detecting parameters of filling slurry curing process; 301, porous stainless steel tube; 302, stone cultural relic; 303, cracks in stone cultural relic; 304, filling slurry; 305, modem; 306, computer; 308, through hole; 400, epoxy resin. DETAILED DESCRIPTION

[0061] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0062] It should be noted that similar numbers and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. In the description of the present invention, it should be noted that the orientation or position relationship indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or position relationship shown in the drawings, or the orientation or position relationship in which the invention product is usually placed when used, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance. In addition, the terms "horizontal", "vertical", etc. do not mean that the components are absolutely horizontal or suspended, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted. In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0063] The present invention can be applied to the repair of cracks in stone cultural relics, and solves the technical problem that in the process of repairing stone cultural relics 302 by grouting repair, the existing detection technology is difficult to achieve online in-situ real-time detection of key parameters such as temperature, humidity and micro-strain during the curing process of grouting materials.

[0064] See also Figures 1 to 4 Based on the technical problems solved above, the present invention discloses an in-situ online detection method for parameters of a stone cultural relic crack filling slurry curing process, comprising the following steps:

[0065] S1. Using fiber Bragg gratings to prepare fiber temperature sensors 101, fiber strain sensors 102, and fiber humidity sensors 103, respectively, and calibrating the fiber temperature sensors, fiber strain sensors, and fiber humidity sensors, respectively, to establish the relationship between temperature and the central resonance wavelength of the fiber Bragg grating in the fiber temperature sensor, the relationship between strain and the central resonance wavelength of the fiber Bragg grating in the fiber strain sensor, and the relationship between humidity and the central resonance wavelength of the fiber Bragg grating in the fiber humidity sensor;

[0066] S2, integrating and packaging the optical fiber temperature sensor 101, the optical fiber humidity sensor 103 and the optical fiber strain sensor 102 prepared in step S1 to obtain a filling slurry curing process parameter detection device 300;

[0067] S3, building a stone cultural relic crack filling slurry curing process parameter online detection system, using multiple filling slurry curing process parameter detection devices 300 prepared in step S2, and vertically placing them at different heights in the stone cultural relic crack 303, respectively, so that the placement position remains unchanged; connecting each filling slurry curing process parameter detection device 300 to the corresponding signal input terminal of the modem 305, and connecting the signal output terminal of the modem 305 to the signal input terminal of the computer 306;

[0068] S4, preparing a filling slurry 304, and uniformly injecting the filling slurry 304 into the fissure 303 of the stone cultural relic under a constant temperature and humidity environment;

[0069] S5. The drift data of the central wavelengths corresponding to the optical fiber temperature sensor 101, the optical fiber strain sensor 102 and the optical fiber humidity sensor 103 in each filling slurry curing process parameter detection device 300 are collected by a modem 305, and demodulated to obtain demodulated data information; the demodulated data information is then transmitted to a computer 306, and the computer 306 calculates the filling slurry curing process parameters at different height positions of the stone cultural relic crack 303 according to the relationship between temperature and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber temperature sensor, the relationship between strain and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber strain sensor, and the relationship between humidity and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber humidity sensor. The filling slurry curing process parameters include the temperature change, strain change and humidity change of the filling slurry during the curing process.

[0070] This solution discloses an optical fiber detection method for the temperature, humidity and micro-strain inside the slurry 304 (e.g., water glass slurry) during the solidification process of the slurry 304 filling the crack 303 of the stone cultural relic 302. The method uses a fiber Bragg grating fiber temperature sensor 101, a fiber Bragg grating strain sensor 102 and a fiber Bragg grating fiber humidity sensor 103 to perform online in-situ measurement of the temperature, humidity and micro-strain of the slurry 304 filling the crack 303 of the simulated sandstone cultural relic during the solidification process.

[0071] During detection, the optical fiber humidity sensor 103 mainly responds to the three change information of temperature, humidity and micro-strain inside the slurry, the strain sensor 102 mainly responds to the two change information of temperature and strain inside the slurry, and the optical fiber temperature sensor 101 only responds to the temperature change information of the slurry. The optical fiber temperature sensor 101 has two functions. The first function is to measure the temperature change during the slurry curing process, and the second function is to serve as a temperature compensation unit of the strain sensor 102 and the optical fiber humidity sensor 103 to eliminate the influence of the slurry temperature change on the strain and humidity measurement results. The strain sensor 102 has two functions. The first function is to measure the strain change inside the slurry curing, and the second function is to serve as a strain compensation unit of the optical fiber humidity sensor 103 to eliminate the influence of the slurry strain change on the humidity measurement results.

[0072] The present invention will provide important support for evaluating the effectiveness of treating rock fissure diseases in stone cultural relics, and has great scientific significance and engineering application value.

[0073] Specifically, the curing process parameters of the filling slurry 304 include the temperature, humidity and microstrain of the filling slurry 304 .

[0074] Specifically, in step S1, the structure of the optical fiber temperature sensor 101 is shown in Figure 1, including an untreated bare fiber Bragg grating 200, the bare fiber Bragg grating 200 includes a core 201, the core 201 has a grating area 202, the core 201 is coated with a cladding 203 on the periphery, the cladding 203 is coated with a coating layer 204 on the periphery, the stainless steel capillary 205 is sleeved on the periphery of the coating layer corresponding to the grating area 202, and both ends of the stainless steel capillary 205 are sealed.

[0075] Preferably, in step S1, the optical fiber temperature sensor 101 is used to monitor the temperature of the slurry curing process and eliminate the influence of temperature on the humidity and strain detection results, that is, the optical fiber temperature sensor 101 is used as the optical fiber temperature sensor 101 and also serves as a temperature compensation unit of the optical fiber humidity sensor 103 and the optical fiber strain sensor 102; the optical fiber temperature sensor 101 is prepared by the following method: an untreated bare fiber Bragg grating 200 is used, and then a stainless steel capillary 205 is used to seal and package the grating area 202 of the bare fiber Bragg grating 200 to obtain the optical fiber temperature sensor 101; before packaging, the bare fiber Bragg grating 200 is temperature calibrated to establish the relationship between the temperature and the central resonance wavelength of the bare fiber Bragg grating 200 to achieve accurate temperature detection and temperature compensation.

[0076] Specifically, the operation method of using the stainless steel capillary 205 to seal and package the grating area 202 of the bare fiber Bragg grating 200 is: first, the stainless steel capillary 205 is sleeved on the outer periphery of the grating area 202 of the bare fiber Bragg grating 200, and then the two ends of the stainless steel capillary 205 corresponding to the two ends of the grating area 202 are sealed with epoxy resin 400 glue.

[0077] The stainless steel capillary 205 is used to encapsulate the grating region 202 of the bare fiber Bragg grating 200 in order to eliminate the influence of stress on the detection result during the detection process; at the same time, the two ends are sealed with epoxy resin 400 glue to prevent the filling slurry 304 from entering the stainless steel capillary 205 during the detection process.

[0078] Specifically, in one embodiment of the stainless steel capillary 205 , the stainless steel capillary 205 with an inner diameter of 400-600 μm and a length of 1.5-2.5 cm is used to encapsulate the fiber grating region 202 .

[0079] Preferably, in step S2, the optical fiber strain sensor 102 is used to monitor the strain of the filling slurry 304 during the curing process and eliminate the influence of the strain on the humidity detection result, that is, the optical fiber strain sensor 102 is used as the optical fiber strain sensor 102 and also serves as the temperature compensation unit of the optical fiber humidity sensor 103; the optical fiber strain sensor 102 directly uses the unprocessed bare fiber Bragg grating 200 without any further processing.

[0080] Specifically, in step S3, the structure of the optical fiber humidity sensor 103 is shown in Figure 2 .

[0081] Preferably, in step S3, the optical fiber humidity sensor 103 is prepared by the following method:

[0082] A1. A bare fiber Bragg grating 200 is used and pre-processed. The bare fiber Bragg grating 200 includes a core 201. The core 201 has a grating region 202. The core 201 is coated with a cladding 203. The cladding 203 is coated with a coating layer 204. The cladding 203 and the coating layer structure 204 corresponding to the grating region 202 are removed.

[0083] A2, treating the pretreated fiber Bragg grating with silane to enhance the adhesion strength of the fiber Bragg grating surface;

[0084] A3, preparing chitosan-polyvinyl alcohol moisture-sensitive material to obtain chitosan-polyvinyl alcohol hydrogel;

[0085] A4. The chitosan-polyvinyl alcohol hydrogel is uniformly coated on the peripheral surface corresponding to the grating area 202 of the fiber Bragg grating treated with silane, and then dried to form a humidity-sensitive film 206 on the peripheral surface corresponding to the grating area 202 of the fiber Bragg grating, thereby obtaining an optical fiber humidity-sensitive sensor 103.

[0086] Specifically, in step A1, the fiber Bragg grating is preprocessed by the following method:

[0087] The fiber Bragg grating is immersed in 95-98% concentrated sulfuric acid for 60-70 minutes to remove all polyacrylate coating layers; the fiber grating area is immersed in anhydrous ethanol and deionized water for shaking cleaning for 8-10 minutes and then dried at room temperature for use.

[0088] Specifically, in step A2, the pretreated fiber Bragg grating is subjected to silane treatment using the following method:

[0089] In order to improve the adhesion strength of the moisture-sensitive film on the optical fiber surface, the fiber Bragg grating was placed in 10% to 12% silane coupling agent for 20 to 30 minutes, then the optical fiber was taken out and cleaned with deionized water, and finally placed in a vacuum drying oven at 90 to 100°C for 10 to 15 minutes before being taken out for use.

[0090] Preferably, in step A3, the chitosan-polyvinyl alcohol humidity-sensitive material is prepared by the following method:

[0091] A3.1. Add chitosan powder to glacial acetic acid solution and stir evenly at room temperature to obtain chitosan solution;

[0092] A3.2. Add polyvinyl alcohol powder to deionized water and stir evenly in a water bath to obtain a polyvinyl alcohol solution;

[0093] A3.3. Add the polyvinyl alcohol solution dropwise into the prepared chitosan solution and stir evenly at room temperature to obtain chitosan-polyvinyl alcohol hydrogel.

[0094] Preferably, in step A3, the mass ratio of chitosan to polyvinyl alcohol is in the range of 4.5:1 to 7.2:1, preferably 4.5:1.

[0095] Preferably, in step A3.1, the mass fraction of the glacial acetic acid solution is in the range of 2% to 5%.

[0096] Preferably, in step A3.2, the mass fraction of the polyvinyl alcohol solution is in the range of 10% to 11%.

[0097] As one of the embodiments for preparing chitosan-polyvinyl alcohol humidity-sensitive materials, 1-2 g of chitosan powder is added to 20-25 ml of glacial acetic acid solution with a mass fraction of 2% to 5%, and stirred at room temperature for 4-5 hours; then 1.2-1.5 g of polyvinyl alcohol powder is weighed and added to 10-12 ml of deionized water, and stirred in a 90-100°C water bath for 2-3 hours; finally, 2-2.5 ml of polyvinyl alcohol solution is taken out and dripped into the prepared chitosan solution, and then stirred at room temperature for 5-6 hours to obtain a chitosan-polyvinyl alcohol hydrogel; in this embodiment, the mass ratio of chitosan to polyvinyl alcohol is in the range of 4.67:1 to 7.2:1.

[0098] Specifically, in step A4, the chitosan-polyvinyl alcohol moisture-sensitive material is coated by the pulling method. Specifically, 0.1-0.2 g of the hydrogel is clamped with tweezers, and the tip of the tweezers is controlled to slowly pull along the outer peripheral surface corresponding to the grating area of ​​the fiber Bragg grating treated with silane, and then placed in a drying oven at 60-70° C. for 20-30 minutes; the above operation is repeated 5-6 times, and finally a thin film is formed around the fiber Bragg grating area. Figure 2 shown.

[0099] The working principles of the optical fiber temperature sensor and the optical fiber strain sensor are analyzed as follows.

[0100] The resonant center wavelength (λ B ) and the effective refractive index of the optical fiber (n eff ) and the grating period (Λ) show a linear relationship, and its expression is:

[0101] λ B =2n eff Λ (1)

[0102] When the external temperature changes, the effective refractive index of the grating will change; at the same time, thermal expansion can also change the grating period, so temperature changes will cause the central wavelength of the fiber Bragg grating to drift.

[0103] The fiber Bragg grating in the fiber temperature sensor is only affected by temperature. Then, when only affected by temperature, the total drift (Δλ) of the fiber Bragg grating wavelength is B_1 )for:

[0104]

[0105] In formula (3), α is the thermal expansion coefficient of the optical fiber material, is the thermo-optic coefficient, ΔT is the temperature change, K T_1 is the fiber Bragg grating temperature sensitivity coefficient of the fiber temperature sensor, where the fiber Bragg grating temperature sensitivity coefficient K T_1 It is expressed as:

[0106]

[0107] In formula (3), λ B_1 represents the resonant center wavelength of the fiber Bragg grating in the fiber temperature sensor, α is the thermal expansion coefficient of the fiber material, is the thermo-optical coefficient.

[0108] However, optical fiber has a photoelastic effect, and strain can make λ B Therefore, when the optical fiber is affected by external stress, it is sensitive to both strain and temperature. The drift of the Bragg center wavelength of the fiber Bragg grating of the optical fiber strain sensor (Δλ B-2 ) is defined as:

[0109]

[0110] In formula (4), P ε is the effective elastic-optical coefficient of the optical fiber, Δε is the strain change of the optical fiber, K ε_1is the fiber Bragg grating strain sensitivity coefficient of the optical fiber strain sensor, K T_2 is the temperature sensitivity coefficient of the fiber Bragg grating of the optical fiber strain sensor.

[0111] Among them, the fiber Bragg grating strain sensitivity coefficient K of the optical fiber strain sensor is ε_1 and temperature sensitivity coefficient K T_2 Respectively expressed as:

[0112] K ε_1 =λ B-2 (1-P ε ) (5)

[0113]

[0114] In formulas (5) and (6), λ B-2 represents the resonant center wavelength of the fiber Bragg grating in the optical fiber strain sensor, P ε is the effective elastic-optical coefficient of the optical fiber, α is the thermal expansion coefficient of the optical fiber material, is the thermo-optical coefficient.

[0115] The working principle of the optical fiber humidity sensor is analyzed as follows.

[0116] The optical fiber humidity sensor utilizes the strain-sensitive properties of humidity-sensitive materials and fiber Bragg gratings to detect humidity. The chitosan-polyvinyl alcohol hydrogel expands and shrinks when it absorbs moisture according to changes in external humidity, thereby generating axial stress of stretching or shrinking and transmitting it to the fiber Bragg grating, thereby causing the center wavelength to drift.

[0117] Therefore, the total drift of the fiber Bragg grating wavelength of the fiber humidity sensor (Δλ B_3 ) can be defined as:

[0118]

[0119] In formula (7), λ B-3 represents the resonant center wavelength of the fiber Bragg grating in the fiber humidity sensor, ε RH , ε T and Δε respectively represent the wet expansion coefficient, thermal expansion coefficient and stress change of the fiber Bragg grating itself after coating with chitosan-polyvinyl alcohol hydrogel.

[0120]

[0121] In the above formulas (8) and (9), A M and A f are the cross-sectional areas of the moisture-sensitive material film and the optical fiber respectively; E M and E fare the Young's modulus of the moisture-sensitive material film and the optical fiber respectively; α M(RH) and α M(T) are the moisture expansion coefficient and thermal expansion coefficient of the humidity sensitive film respectively; α f(RH) and α f(T) are the moisture expansion coefficient and thermal expansion coefficient of the optical fiber respectively.

[0122] Since bare FBG is insensitive to humidity, the moisture expansion coefficient α f(RH) is 0, and from formula (7) it is:

[0123] Δλ B_3 =λ B_3 (K RH ΔRH+K ε_2 Δε+K T_3 ΔT) (10)

[0124] In formula (10), λ B-3 represents the resonant center wavelength of the fiber Bragg grating in the fiber humidity sensor, ΔRH is the humidity change; K RH , K ε_2 and K T_3 Respectively represent the sensitivity coefficients of humidity, strain and temperature of the fiber Bragg grating of the optical fiber humidity sensor, where K RH , K ε_2 and K T_3 They can be expressed as:

[0125]

[0126] K ε_2 =λ B_3 (1-P ε ) (12)

[0127]

[0128] In formulas (11)-(13), P ε is the effective elastic-optic coefficient of the fiber Bragg grating; r f is the fiber radius; t is the thickness of the humidity sensitive film; C0 is the surface bonding coefficient between the fiber grating and the humidity sensitive film; E M and E f are the Young's modulus of the moisture-sensitive material film and the optical fiber respectively; α M(RH) A is the moisture expansion coefficient of the moisture sensitive film; M and A f are the cross-sectional areas of the moisture-sensitive material film and the optical fiber respectively; α M(T) and α f(T) are the thermal expansion coefficients of the humidity sensitive film and optical fiber, respectively; is the thermo-optical coefficient.

[0129] As a preference, see Figure 3 In step S2, the integrated packaging of the optical fiber temperature sensor 101, the optical fiber humidity sensor 103 and the optical fiber strain sensor 102 is performed by the following method: the grating areas 202 corresponding to the optical fiber temperature sensor 101, the optical fiber humidity sensor 103 and the optical fiber strain sensor 102 are wrapped by a porous stainless steel tube 301, and at the same time, the optical fiber pigtails corresponding to the optical fiber temperature sensor 101, the optical fiber humidity sensor 103 and the optical fiber strain sensor 102 are extended from the same end of the porous stainless steel tube 301, and the tube wall of the porous stainless steel tube 301 is evenly opened with a plurality of through holes 308; one end of each optical fiber pigtail extending out of the porous stainless steel tube 301 is sealed.

[0130] The porous stainless steel tube 301 can effectively protect each sensor during measurement. The purpose of sealing one end of the porous stainless steel tube 301 is to fix each optical fiber pigtail so that the relative position between each optical fiber pigtail remains unchanged. In addition, during measurement, the filling slurry 304 can enter the porous stainless steel tube 301 from the other end and contact each sensor, so that the temperature, humidity and micro-strain at the same position can be measured simultaneously.

[0131] Specifically, the specifications of the porous stainless steel tube 301 used are an inner diameter of 3 to 4 mm and a length of 2 to 3 cm.

[0132] Preferably, in step S5, the vertical spacing between two adjacent filling slurry curing process parameter detection devices 300 is in the range of 10 to 30 mm.

[0133] Preferably, in step S5, the vertical spacing between two adjacent filling slurry curing process parameter detection devices 300 is in the range of 25 to 30 mm.

[0134] For details, please refer to Figure 4 , the filling slurry 304 is uniformly injected into the cracks 303 of the stone cultural relic under constant temperature and humidity conditions.

[0135] Preferably, in step S6, the filling slurry 304 uses water glass slurry, and the water glass slurry is prepared by the following method: first, dissolve sodium silicate powder in deionized water, stir evenly at room temperature to obtain a sodium silicate solution; use ultrasonic treatment to degas the sodium silicate solution, and let it stand after ultrasonic treatment; add ethylene glycol diacetate to the sodium silicate solution, and stir evenly in a water bath to obtain water glass slurry.

[0136] Specifically, as one of the embodiments of the water glass slurry, 8-9g of sodium silicate powder is dissolved in 20-25ml of deionized water, stirred at room temperature for 60-70min, and ultrasonically treated for 50-60min to achieve the degassing effect. Let it stand for 10-20min for standby use. 15-20ml of deionized water and 3.5-4ml of ethylene glycol diacetate with a mass fraction of 98-99% are added to the sodium silicate solution, and stirred in a 35-40°C water bath for 3-5min.

[0137] Preferably, in step S5, when the computer calculates the filling slurry curing process parameters at different height positions of the stone cultural relic cracks, the optical fiber temperature sensor and the optical fiber strain sensor are used as the temperature compensation unit and the strain compensation unit of the optical fiber humidity sensor respectively, and the pre-constructed matrix model is performed to obtain the filling slurry curing process parameters; the matrix model can be established by formula (2), formula (4) and formula (10) as follows:

[0138]

[0139] In formula (14), Δλ B_1 is the total drift of the fiber Bragg grating wavelength of the fiber temperature sensor, Δλ B_2 is the total drift of the fiber Bragg grating wavelength of the optical fiber strain sensor, Δλ B_3 is the total drift of the fiber Bragg grating wavelength of the fiber humidity sensor, ΔT is the temperature change; Δε is the strain change, ΔRH is the humidity change; K T_1 is the fiber Bragg grating temperature sensitivity coefficient of the fiber temperature sensor, the expression is referred to formula (3), K ε_1 , K T_2 are the fiber Bragg grating strain sensitivity coefficient and temperature sensitivity coefficient of the optical fiber strain sensor, respectively. The expressions refer to equations (5) and (6), K RH , K ε_2 and K T_3 represent the sensitivity coefficients of humidity, strain and temperature of the fiber Bragg grating of the optical fiber humidity sensor respectively, and their expressions refer to equations (11), (12) and (13).

[0140] The detection principle of the present invention is as follows: the present invention uses three types of optical fiber sensors, including a strain sensor composed of an untreated optical fiber Bragg grating, an optical fiber temperature sensor 101 composed of an untreated bare optical fiber Bragg grating 200 and a stainless steel capillary 205 package, and an optical fiber humidity sensor 103 composed of an optical fiber Bragg grating with a coating removed and humidity-sensitive materials chitosan / polyvinyl alcohol. These sensors are packaged in a porous stainless steel tube 301, forming a device capable of online in-situ detection of parameters of the curing process of the filling slurry in the cracks of stone cultural relics.

[0141] When in use, the detection device is placed in the crack 303 and the filling slurry 304 is injected. During the detection process, the sensor is continuously in contact with the filling slurry 304. When the temperature and humidity of the filling slurry 304 change, or when expansion stress or contraction stress is generated, these changes will cause the central wavelength of the sensor fiber grating to change accordingly. Specifically, the optical fiber temperature sensor 101 is mainly affected by temperature because it is encapsulated by the stainless steel capillary 205. The strain sensor is affected by both temperature and strain, but temperature compensation can be achieved through the detection value of the optical fiber temperature sensor 101 at the same position. The optical fiber humidity sensor 103 is affected by the three parameters of temperature, humidity and strain at the same time, and temperature compensation and strain compensation can be achieved through the detection values ​​of the optical fiber temperature sensor 101 and the optical fiber strain sensor 102 at the same height. The drift of the central wavelength is collected by the fiber grating demodulator, and the demodulated data is transmitted to the computer 306, so that the change information of each parameter during the curing process can be calculated.

[0142] The in-situ online detection method for parameters of the curing process of the slurry filling the cracks of stone cultural relics disclosed in the present invention has the following technical effects:

[0143] 1. It can simultaneously monitor multiple key parameters of the filling slurry, such as temperature, humidity, strain, etc., and provide comprehensive monitoring data for the restoration and protection of stone cultural relics. The fiber Bragg grating sensor is very sensitive to changes in temperature, humidity and strain, and can detect tiny changes with high sensitivity. In addition, the fiber optic sensor is not affected by electromagnetic interference, can work stably in a complex electromagnetic environment, has strong anti-interference ability, and has good long-term stability.

[0144] 2. Each sensor is encapsulated in a porous stainless steel tube and can be used in harsh environments, such as high humidity or corrosive environments. It has strong environmental adaptability. The strain sensor can achieve temperature compensation through the detection value of the optical fiber temperature sensor at the same position, and the optical fiber humidity sensor can achieve temperature compensation and strain compensation through the detection values ​​of the optical fiber temperature sensor and the optical fiber strain sensor at the same height, further improving the accuracy of the measurement.

[0145] 3. In-situ detection can be carried out by simply placing the device for filling the parameters of the slurry curing process in the cracks without destroying the structure of the cultural relics. The fiber grating demodulator can collect data in real time, which is easy to process and analyze by computer, convenient for data management and decision support, and can realize continuous monitoring of the curing process, and can realize in-situ online detection.

[0146] 4. The position and quantity of the devices for each filling slurry curing process parameter can be adjusted as needed to meet different monitoring needs. They can also be integrated with other monitoring systems or automatic control systems to achieve more advanced monitoring and control functions.

[0147] 5. Compared with traditional monitoring methods, the optical fiber sensor of the present invention provides a cost-effective solution.

[0148] In order to further illustrate the method of the present invention, the present invention discloses the following application examples.

[0149] The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry disclosed in this embodiment comprises the following steps:

[0150] Step A, preparing an optical fiber temperature sensor 101, which is used to monitor the temperature of the slurry curing process and eliminate the influence of temperature on humidity and strain detection results, that is, the optical fiber temperature sensor 101 is used as the optical fiber temperature sensor 101, and also serves as a temperature compensation unit of the optical fiber humidity sensor 103 and the optical fiber strain sensor 102; specifically, the optical fiber temperature sensor 101 is prepared by the following method:

[0151] An untreated bare fiber Bragg grating 200 is used, and then a stainless steel capillary 205 with an inner diameter of 0.5 mm and a length of 20 mm is used to seal and package the grating area 202 of the bare fiber Bragg grating 200 to obtain an optical fiber temperature sensor 101; before packaging, the bare fiber Bragg grating 200 is temperature calibrated to establish a relationship between the temperature and the central resonance wavelength of the bare fiber Bragg grating 200; specifically, the operation method of sealing and packaging the grating area 202 of the bare fiber Bragg grating 200 with the stainless steel capillary 205 is as follows: first, the stainless steel capillary 205 is sleeved on the outer periphery of the grating area 202 of the bare fiber Bragg grating 200, and then the two ends of the stainless steel capillary 205 corresponding to the two ends of the grating area 202 are sealed with epoxy resin 400 glue. The stainless steel capillary 205 is used to encapsulate the grating region 202 of the bare fiber Bragg grating 200 in order to eliminate the influence of stress on the detection result during the detection process; at the same time, the two ends are sealed with epoxy resin 400 glue to prevent the filling slurry 304 from entering the stainless steel capillary 205 during the detection process.

[0152] Step B, preparing an optical fiber strain sensor 102 for monitoring the strain during the curing process of the filling slurry 304 and eliminating the influence of the strain on the humidity detection result, that is, the optical fiber strain sensor 102 is used as the optical fiber strain sensor 102 and also serves as a strain compensation unit of the optical fiber humidity sensor 103; the optical fiber strain sensor 102 uses an untreated bare optical fiber Bragg grating 200; strain calibration is performed on the optical fiber strain sensor 102 to establish the relationship between the strain and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber strain sensor 102;

[0153] Step C, preparing an optical fiber humidity sensor 103 for responding to temperature change information, humidity change information and microstrain change information; establishing a relationship between humidity and the central resonant wavelength of the fiber Bragg grating in the optical fiber humidity sensor 103, specifically, comprising the following steps:

[0154] C1. Use a bare fiber Bragg grating 200 and pre-treat the bare fiber Bragg grating 200, wherein the bare fiber Bragg grating 200 comprises a core 201, the core 201 has a grating region 202, the core 201 is coated with a cladding 203 on its periphery, the cladding 203 is coated with a coating layer 204 on its periphery, and the cladding 203 and the coating layer structure corresponding to the grating region 202 are removed; Specifically, immerse the fiber Bragg grating in 98% concentrated sulfuric acid for 60 minutes to remove all polyacrylate coating layers, and then immerse the fiber grating region 202 in anhydrous ethanol and deionized water for shaking and cleaning for 10 minutes, and then dry it at room temperature for use;

[0155] C2. The pretreated fiber Bragg grating is subjected to silane treatment to enhance the adhesion strength of the fiber Bragg grating surface; specifically, the fiber Bragg grating is placed in a 10% silane coupling agent for 30 minutes, then the fiber is taken out and cleaned with deionized water, and finally placed in a vacuum drying oven and dried at 90° C. for 15 minutes before being taken out for use;

[0156] C3, preparing chitosan-polyvinyl alcohol humidity-sensitive material to obtain chitosan-polyvinyl alcohol hydrogel;

[0157] Specifically, 1g of chitosan powder was added to 20ml of 4% glacial acetic acid solution and stirred at room temperature for 4h. 1.5g of polyvinyl alcohol powder was weighed and added to 12ml of deionized water and stirred in a 95°C water bath for 3h. Finally, 2ml of polyvinyl alcohol solution was taken out and dropped into the prepared chitosan solution and stirred at room temperature for 6h to obtain chitosan-polyvinyl alcohol hydrogel. The mass ratio of chitosan to polyvinyl alcohol in the chitosan-polyvinyl alcohol hydrogel prepared in this embodiment is 4.5:1.

[0158] C4. The chitosan-polyvinyl alcohol hydrogel is uniformly coated on the peripheral surface corresponding to the grating area 202 of the fiber Bragg grating treated with silane, and then dried to form a moisture-sensitive film 206 on the peripheral surface corresponding to the grating area 202 of the fiber Bragg grating, thereby obtaining the optical fiber moisture-sensitive sensor 103; specifically, the moisture-sensitive material is coated by a pulling method, and the tip of the tweezers is controlled to slowly pull along the peripheral surface corresponding to the grating area 202 of the fiber Bragg grating treated with silane, and then placed in a 60°C drying oven for 20 minutes. Repeat the above operation 5 times, and finally form a thin film around the fiber Bragg grating area 202.

[0159] Step D: Integrate the optical fiber temperature sensor 101, the optical fiber humidity sensor 103 and the optical fiber strain sensor 102 prepared in steps A to C to obtain a filling slurry curing process parameter detection device 300;

[0160] Specifically, a porous stainless steel tube 301 with an inner diameter of 3 mm and a length of 25 mm is used to wrap the fiber grating region 202 of the fiber optic temperature sensor 101, the fiber optic humidity sensor 103 and the fiber optic strain sensor 102, and one end of the optical fiber is fixed with epoxy resin 400.

[0161] Step E: Use three filling slurry curing process parameter detection devices 300 prepared in step D, and vertically place them at different heights in the stone cultural relic crack 303, so that the placement position remains unchanged, and the vertical spacing range between two adjacent filling slurry curing process parameter detection devices 300 is 30 mm; connect each filling slurry curing process parameter detection device 300 to the corresponding signal input terminal of the modem 305, and connect the signal output terminal of the modem 305 to the signal input terminal of the computer 306;

[0162] Step F, preparing water glass slurry as the filling slurry 304 for the stone cultural relic fissure 303, and uniformly injecting the filling slurry 304 into the stone cultural relic fissure 303 under constant temperature and humidity conditions;

[0163] Specifically, the preparation process of water glass slurry is as follows: 8.5g sodium silicate powder is dissolved in 20ml deionized water, stirred at room temperature for 60min, ultrasonically treated for 50min to achieve the effect of degassing, and allowed to stand for 10min for use. 15ml deionized water and 3.5ml ethylene glycol diacetate with a mass fraction of 98% are added to the sodium silicate solution, and stirred in a 35°C water bath for 3min.

[0164] Step G: The drift data of the central wavelength corresponding to the optical fiber temperature sensor 101, the optical fiber strain sensor 102 and the optical fiber humidity sensor 103 in each filling slurry curing process parameter detection device 300 are collected by the modem 305, and demodulated to obtain the demodulated data information; the demodulated data information is then transmitted to the computer 306, and the computer 306 calculates the curing process parameters of the filling slurry 304 at different height positions of the stone cultural relic crack 303.

[0165] The test results of this embodiment are analyzed as follows: Figures 5 to 7 shown.

[0166] Figure 5It shows the temperature distribution inside the slurry during the solidification process of water glass. The results show that the temperature change trend at different heights is first rising and then falling, and the temperature change at 2 cm is the most obvious. The reason is that the silicate generated by water glass slurry and acetic acid has a large density and is unstable, and decomposes into silicon dioxide, causing the slurry at the bottom to solidify first, so the temperature rises first. The bottom part has the least contact with the air and is least affected by the external temperature. The slurry at the top has more contact with the outside world, and the solidification process continuously releases heat to the outside world, so the temperature is the lowest.

[0167] Figure 6 It indicates the humidity distribution inside the slurry during the curing process of water glass. The results show that from the beginning to the end of curing, the humidity inside the slurry gradually decreases and the rate gradually slows down. This is because as the temperature first increases and then decreases, the hydrolysis reaction rate inside the slurry gradually decreases and the water evaporation rate caused by temperature decreases. The humidity of the slurry at 2 cm begins to decrease first, but as the curing progresses, the humidity of the slurry at 8 cm decreases the fastest.

[0168] The reasons are: (1) The silicate generated by water glass slurry and acetic acid has a high density and is unstable, decomposing into silicon dioxide, causing the slurry at the bottom to solidify first, so the humidity decreases first; (2) The slurry at the top has the largest contact area with the external environment and constantly reacts with carbon dioxide, so the moisture loss rate at the top is the fastest.

[0169] Figure 7 The figure shows the stress distribution inside the slurry during the solidification process of water glass in sandstone samples with different crack sizes. The results show that the shrinkage stress at 2 cm is the largest. The reason is as mentioned above. The solidification of the slurry occurs "from bottom to top". At first, due to the increase in temperature, part of the slurry undergoes "thermal expansion", which in turn generates tensile stress on the stress sensor. When the material at the bottom solidifies, the volume of the bottom shrinks and drives the unsolidified slurry above to produce a downward displacement. Since the water glass slurry has a certain viscosity, the stress sensors at 5 cm and 8 cm will receive a downward tensile stress to offset the shrinkage stress generated by part of the material, and the closer to the top, the greater the tensile stress on the sensor.

[0170] It is understood that the present invention is described by some embodiments, and those skilled in the art are aware that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. Under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. The embodiments described in the present invention are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention generally described and shown in the drawings herein may be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all other embodiments obtained by ordinary technicians in the art without creative work based on the embodiments in the present invention belong to the scope of protection of the present invention.

Claims

1. An in-situ online detection method for parameters of a curing process of a slurry filling crack in stone cultural relics, characterized in that: The following steps are involved: S1. Using fiber Bragg gratings to prepare fiber temperature sensors, fiber strain sensors, and fiber humidity sensors, respectively, and calibrating the fiber temperature sensors, fiber strain sensors, and fiber humidity sensors, respectively, to establish the relationship between temperature and the central resonance wavelength of the fiber Bragg grating in the fiber temperature sensor, the relationship between strain and the central resonance wavelength of the fiber Bragg grating in the fiber strain sensor, and the relationship between humidity and the central resonance wavelength of the fiber Bragg grating in the fiber humidity sensor; S2, integrating the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor prepared in step S1 to obtain a device for detecting parameters of the filling slurry curing process; S3, building an online detection system for the curing process parameters of the filling slurry in the cracks of stone cultural relics, using multiple filling slurry curing process parameter detection devices prepared in step S2, and vertically placing them at different heights in the cracks of stone cultural relics, respectively, so that the placement positions remain unchanged; connecting each filling slurry curing process parameter detection device to the corresponding signal input terminal of the modem, and connecting the signal output terminal of the modem to the signal input terminal of the computer; S4, preparing a filling slurry, and uniformly injecting the filling slurry into the cracks of the stone cultural relics under constant temperature and humidity conditions; S5. The drift data of the central wavelengths corresponding to the optical fiber temperature sensor, the optical fiber strain sensor and the optical fiber humidity sensor in each filling slurry curing process parameter detection device are collected by a modem, and demodulated to obtain demodulated data information; the demodulated data information is then transmitted to a computer, and the computer calculates the filling slurry curing process parameters at different height positions of the stone cultural relic crack according to the relationship between the temperature and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber temperature sensor, the relationship between the strain and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber strain sensor, and the relationship between the humidity and the central resonance wavelength of the optical fiber Bragg grating in the optical fiber humidity sensor. The filling slurry curing process parameters include the temperature change, strain change and humidity change of the filling slurry during the curing process.

2. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 1 is characterized in that: In step S1, the optical fiber temperature sensor is used as an optical fiber temperature sensor and also serves as a temperature compensation unit of the optical fiber humidity sensor and the optical fiber strain sensor; the optical fiber temperature sensor is prepared by the following method: an untreated bare fiber Bragg grating is used, and then a stainless steel capillary is used to seal and package the grating area of ​​the bare fiber Bragg grating to obtain the optical fiber temperature sensor; before packaging, the bare fiber Bragg grating is temperature calibrated to establish the relationship between the temperature and the central resonance wavelength of the bare fiber Bragg grating.

3. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 1 is characterized in that: In step S1, the optical fiber strain sensor is used as an optical fiber strain sensor and also as a strain compensation unit of the optical fiber moisture sensor; the optical fiber strain sensor uses an untreated bare fiber Bragg grating.

4. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 1 is characterized in that: In step S1, the optical fiber humidity sensor is prepared by the following method: A1. Use a bare fiber Bragg grating and pre-process the bare fiber Bragg grating, wherein the bare fiber Bragg grating comprises a core, the core has a grating region, the outer periphery of the core is coated with a cladding, the outer periphery of the cladding is coated with a coating layer, and the cladding and coating layer structure corresponding to the grating region are removed; A2, treating the pretreated fiber Bragg grating with silane to enhance the adhesion strength of the fiber Bragg grating surface; A3, preparing chitosan-polyvinyl alcohol moisture-sensitive material to obtain chitosan-polyvinyl alcohol hydrogel; A4. Evenly apply chitosan-polyvinyl alcohol hydrogel on the peripheral surface corresponding to the grating area of ​​the fiber Bragg grating treated with silane, and then dry it to form a humidity-sensitive film on the peripheral surface corresponding to the grating area of ​​the fiber Bragg grating, thereby obtaining an optical fiber humidity-sensitive sensor.

5. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 4 is characterized in that: In step A3, the chitosan-polyvinyl alcohol humidity-sensitive material is prepared by the following method: A3.

1. Add chitosan powder to glacial acetic acid solution and stir evenly at room temperature to obtain chitosan solution; A3.

2. Add polyvinyl alcohol powder to deionized water and stir evenly in a water bath to obtain a polyvinyl alcohol solution; A3.

3. Add the polyvinyl alcohol solution dropwise into the prepared chitosan solution and stir evenly at room temperature to obtain chitosan-polyvinyl alcohol hydrogel.

6. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 4 or 5, characterized in that: In step A3, the mass ratio of chitosan to polyvinyl alcohol is in the range of 4.5:1 to 7.2:

1.

7. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 5 is characterized in that: In step A3.1, the mass fraction of the glacial acetic acid solution is in the range of 2% to 5%.

8. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 5 is characterized in that: In step A3.2, the mass fraction of the polyvinyl alcohol solution is in the range of 10% to 11%.

9. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 1 is characterized in that: In step S2, the integrated packaging of the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor is performed by the following method: the grating areas corresponding to the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor are wrapped with a porous stainless steel tube, and at the same time, the optical fiber pigtails corresponding to the optical fiber temperature sensor, the optical fiber humidity sensor and the optical fiber strain sensor are extended from the same end of the porous stainless steel tube, and the tube wall of the porous stainless steel tube is evenly provided with a plurality of through holes; and each optical fiber pigtail is extended out of one end of the porous stainless steel tube and sealed.

10. The in-situ online detection method for parameters of the curing process of the stone cultural relic crack filling slurry according to claim 1 is characterized in that: In step S5, when the computer calculates the filling slurry curing process parameters at different height positions of the stone cultural relic cracks, the optical fiber temperature sensor and the optical fiber strain sensor are used as the temperature compensation unit and the strain compensation unit of the optical fiber humidity sensor respectively, and the pre-constructed matrix model is performed to obtain the filling slurry curing process parameters; the matrix model is: In the formula, Δλ B_1 is the total drift of the fiber Bragg grating wavelength of the fiber temperature sensor, Δλ B_2 is the total drift of the fiber Bragg grating wavelength of the optical fiber strain sensor, Δλ B_3 is the total drift of the fiber Bragg grating wavelength of the fiber humidity sensor, ΔT is the temperature change; Δε is the strain change, and ΔRH is the humidity change; K T_1 is the fiber Bragg grating temperature sensitivity coefficient of the fiber temperature sensor, expressed as: K ε_1 , K T_2 are the fiber Bragg grating strain sensitivity coefficient and temperature sensitivity coefficient of the optical fiber strain sensor, respectively, expressed as: K ε_1 =λ B-2 (1-P ε ); K RH , K ε_2 and K T_3 The sensitivity coefficients of humidity, strain and temperature of the fiber Bragg grating of the optical fiber humidity sensor are respectively expressed as: K ε_2 =λ B_3 (1-P ε ); In the above formula, λ B_1 , B-2 , B-3 They represent the resonant center wavelengths of the fiber Bragg gratings in the fiber temperature sensor, fiber strain sensor, and fiber humidity sensor, respectively; α is the thermal expansion coefficient of the optical fiber material, is the thermo-optical coefficient; P ε is the effective elastic-optic coefficient of the fiber Bragg grating, r f is the fiber radius; t is the thickness of the humidity sensitive film, C0 is the surface bonding coefficient between the fiber grating and the humidity sensitive film, E M and E f are the Young's modulus of the moisture-sensitive material film and the optical fiber, α M(RH) A is the moisture expansion coefficient of the moisture sensitive film; M and A f are the cross-sectional areas of the moisture-sensitive material film and the optical fiber, α M(T) and α f(T) are the thermal expansion coefficients of the humidity sensitive film and optical fiber, respectively.

Citation Information

Patent Citations

  • Fiber bragg grating temperature and humidity integrated sensor array and temperature and humidity measuring method

    CN116519060A

  • PH optical fiber sensor and preparation method thereof, and stone cultural relic parameter in-situ detection method

    CN117470837A

  • Humidity optical fiber sensor and preparation method thereof, and stone cultural relic humidity in-situ detection method

    CN117629989A

  • Fiber bragg grating humidity sensor with enhanced sensitivity

    WO2007137429A1

Cited By

  • Multi-state on-line monitoring system and method for molding sand in sand casting process

    CN120351994A